A family cluster of severe acute respiratory syndrome coronavirus 2 infections - Gao, Xuesong (Eur J Clin Microbiol Infect Dis, 2020)
Clinical and epidemiological knowledge of 2019 novel coronavirus disease (COVID-19) is limited. We reported a family cluster of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) cases in Beijing, China. This family comprised three laboratory confirmed cases with clinical symptoms. All three patients had close contact with a relative from Wuhan, Hubei Province. Throat swab samples were all positive for SARS-CoV-2 using real-time reverse transcriptase-polymerase chain reaction assays. Chest computerized tomography revealed ground-glass opacities and consolidation. SARS-CoV-2 infections tend to clusters. Physicians should be aware of contact history so that infected patients can be identified promptly and further spreading prevented.